DNA BARCODING OF MAJOR PESTS OF THE PIGEON PEA Cajanus cajan (L) Millsp USING CO1 GENE - PUSHPARAJ KARTHIKA,; NATRAJ KRISHNAVENI, (International Journal of Pharma and Bio Sciences, 2016)
Six major pests Cajanus cajan (L) Millsp were collected from the agricultural fields of Karamadai, Tamilnadu. DNA was sequenced and identified using CO1 gene. The sequence content, nucleotide information and substantial saturation were studied and utilized for phylogenetic studies. Homology of sequence comparisons was done and the sequence of four species matched exactly with the respective species that existed in the database. However, the nucleotide sequences of two species, Eurybrachys tomentosa and Gametis versicolor were reported for the first time in our study. A strong AT bias was observed among the sequences and the ratio of the substitutions(R) was high in the first and third codon positions. The threshold value was 1.97%, inter and intra nucleotide divergences of the six species were also calculated and no overlap existed among the species. Distinct barcoding gap was noted. High nucleotide diversity P(i) and maximum intraspecific variation was found among the individuals of N. viridula.